Family-centred care for children with traumatic brain injury and/or spinal cord injury: a qualitative study of service provider perspectives during the COVID-19 pandemic. Issue 6 (13th June 2022) - Pollock, Anna; D'Cruz, Kate; Scheinberg, Adam; Botchway, Edith; Harms, Louise; Amor, David J; Anderson, Vicki; Bonyhady, Bruce; Knight, Sarah
Abstract : Objectives: COVID-19 has led to rapid changes in rehabilitation service provision for young people living with traumatic brain and/or spinal cord injury. The aim of this project was to understand the experiences of rehabilitation service providers during the acute response stage of the COVID-19 pandemic. Specifically, we aimed to identify innovative approaches to meeting the ongoing needs of young people with traumatic brain and/or spinal cord injury during this time. Setting: This study was conducted at a research institute and involved remote interviews with key informants around Australia and internationally. Participants: Key informants from 11 services supporting children and/or adolescents with traumatic brain injury and/or spinal cord injury were interviewed using a semistructured interview guide. Interviews were transcribed and analysed using inductive thematic analysis. Results: Three key themes emerged: (1) recognising and responding to the experiences of families during the pandemic, (2) the impact of greater use of telehealth on care delivery, and (3) realising opportunities to enhance family-centred care. Conclusions: These themes capture shifting perspectives and process changes relevant to longer term practice. Research findings suggest opportunities for future service development, enabling service delivery that is more family centred, flexible and efficient in meeting the needs of families. Understanding these experiences and the changed nature of service delivery provides important insights with implications for future service improvement.